PENGUATAN EKONOMI LOKAL MASYARAKAT DESA ADAT GERIANA KAUH - Adveni, Lusia Vreyda; Widiastuti, Ni Putu; Prami, Anak Agung Istri Dyah; Wijana, Putu Ade; Sembiring, Ejasa (Universitas Mataram, 2024)
The Community Service Program (PkM) with the theme Strengthening the Local Economy of the Geriana Kauh Traditional Village Community is implemented by the Runata Business College (STB Runata) with a strong commitment to developing the potential of local human resources. The results of an interview with Indigenous Village Chief Geriana Kauh revealed that in the village there are various craftsmen who are experts in their respective fields, such as Ate craftsmen, bamboo craftsmen, weaving craftsmen, and dodol makers. This training aims to improve the skills of village residents and help them understand the importance of using social media to market local products. Apart from that, simple bookkeeping training helps entrepreneurs and craftspeople in preparing neat and simple financial reports. Village potential mapping is carried out to identify existing strengths, weaknesses, opportunities and challenges, so that effective development strategies can be formulated. Service activities were carried out in Geriana Kauh Village, North Duda, Selat, Karangasem. This activity was carried out on March 23 2024. The total number of participants who attended this activity was 50 (fifty), each consisting of 20 (twenty) people from the Geriana Kauh village community and 30 (thirty) people from STB Runata. The method used to solve the problem is carrying out socialization activities, training and mentoring on social media content and simple bookkeeping. The results of this service are that through a series of education and training, program participants, including craftsmen, entrepreneurs and village youth, gain useful new knowledge and skills. They learn about business financial management, digital marketing via social media, and the importance of mapping local potential.